Tp53 determines the spatial dynamics of M1/M2 tumor-associated macrophages and M1-driven tumoricidal effects - Yi-Jing Hsiao; Min-Shu Hsieh; Gee-Chen Chang; Yin-Chen Hsu; Chia-Yu Wang; Yan-Ming Chen; Yi-Ling Chen; Pan-Chyr Yang; Sung-Liang Yu (Cell Death and Disease)
Abstract The spatial role of M1 and M2 tumor-associated macrophages (M1/M2 TAMs) in precision medicine remains unclear. EGFR and TP53 are among the most frequently mutated genes in lung adenocarcinoma. We characterized the mutation status and density of M1/M2 TAMs within tumor islets and stroma in 117 lung adenocarcinomas using next-generation sequencing and immunohistochemistry, respectively. Stromal M1 TAMs were positively correlated with disease progression and smoking history. In contrast, islet M1/M2 TAMs were predominantly found in tumors with wild-type TP53 (wtp53) but not associated with EGFR status. The presence of wtp53 was associated with the spatial distribution of M1/M2 TAMs in tumor islets and stroma. Additionally, dominance of islet M1 TAMs and M1-signature were significantly associated with improved survival in patients with wtp53 lung adenocarcinoma, unlike in those with mutant TP53. Conditioned medium from M1 macrophages (M1 CM) induced apoptosis in wtp53 cells through increased p53 accumulation. We found that interferons in M1 CM activate JAK1/TYK2 via IFNARs, leading to enhanced STAT1 expression and Y701 phosphorylation. This activation facilitates p53-STAT1 interactions, reduces the interaction between p53 and MDM2, and subsequently decreases p53 ubiquitination. M1 CM inhibited tumorigenesis, and silencing p53 reduced the anti-tumor efficacy of polyinosinic:polycytidylic acid (poly I:C) in vivo. Furthermore, higher M1-signature was significantly associated with better responses and survival following anti-PD1 treatment in wtp53 melanomas. IFNs/STAT1/p53 signaling was critical for the anti-tumor activity of M1 macrophages. These findings suggest that p53 modulates the spatial balance of M1/M2 TAMs, and the tumoricidal effects of M1 TAMs depend on p53 status. Thus, p53 companion diagnostics could facilitate the development of M1-oriented therapies, which may be particularly beneficial for wtp53 patients when combined with immunotherapy.